Free Radicals and Diseases 2016
DOI: 10.5772/63669
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dietary Antioxidant Agents in Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is defined as the atrophy of the kidney or progressive decline of renal function mainly caused by chronic diseases such as diabetes mellitus and hypertension. CKD affects more than 10% of the world's population. Moreover, there is no single treatment to improve kidney function in CKD patients. Consequently, this condition is considered a worldwide public health problem. The development of novel CKD therapies is highly needed because current treatment methods are ineffective. Since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 71 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…A cup of 30 grams of raw (uncooked) lentils has 203 mg of potassium and 84.3 mg of phosphorus, making them a food high in potassium, phosphorus, purines, and oxalate that may limit their use or need the use of phosphate binders and potassium-lowering medications [12] .…”
Section: Discussionmentioning
confidence: 99%
“…A cup of 30 grams of raw (uncooked) lentils has 203 mg of potassium and 84.3 mg of phosphorus, making them a food high in potassium, phosphorus, purines, and oxalate that may limit their use or need the use of phosphate binders and potassium-lowering medications [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Supplement of dietary antioxidants has been identified as an effective therapeutic approach in reducing oxidative stress caused by the doxorubicin‐induced nephrotoxicity. A number of studies were reported on investigation of nephroprotective activity of dietary antioxidants such as curcumin, resveratrol, quercetin, and proanthocyanidins in doxorubicin‐induced experimental nephrotoxicity model (Benzer et al., 2018; El‐Sayed et al 2017; Eugenio‐Perez et al., 2016; Heeba and Mahmoud 2014; Shahbazi et al 2020). Hence, in this study, the potential protective effect of V. zizanioides root extract was investigated against the experimental model of doxorubicin‐induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from Inulin, other phytochemicals such as phenolics (cathecins, flavonoids, etc.) are also known to have significant roles in treating DM2 and related diseases such as chronic kidney disease (CKD) and Nonalcoholic Fatty Liver (NAFL) disease through their antioxidant properties [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Therefore, investigating the JA tuber proteome might provide new insights into the protein components and their healing properties.…”
Section: Introductionmentioning
confidence: 99%